Evaluasi Efektivitas Kinerja Filter Press Plate and Frame pada Proses Pemanenan Spirulina sp - Lukman Nulhakim; I Dewa Ray Rahendra Astawa; Dantje Marten (Jurnal Migasian, 2022)
Spirulina sp can be used as raw material for making masks and medicines. This research wasconducted to determine the effectiveness of the performance of using a Filter Press (plate and frame) in harvesting Spirulina sp. In this study, Spirulina was cultured in 60 L styrofoam containers with different photoperiods (light/T and dark/G), for 12 hours per day (12T-12G). Parameters observed include dry biomass. For 12 hours per day (12T-12G), Press Filters with 2 and 3 plates were used and pressure of procrsess are 1, 1.5, and 3 Psi. In this study, Spirulina sp can grow well with a concentration of 0.6636 gr mL-1. The filter press plate and frame can be used to harvest Spirulina Sp with the optimum conditions for the Spirulina filtration process by pressing two psi and the number of plates 3, where the highest amounts of filtered Spirulina are 39.653 g with a filtering time of 2 x 103 seconds.